A germanium phosphide / carbon nanotube composite material, a preparation method and application thereof

CN122930848APending Publication Date: 2026-10-16CHANGZHOU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410944543.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]针对上述现有技术中的锗基材料在充放电循环过程中的会发生严重的体积膨胀,导致电极粉化的机械不稳定和容量快速衰减的问题,本发明提供一种磷化锗/碳纳米管复合材料及其制备方法和应用

Benefits of technology

[0036] This invention uses GeP nanosheets with a two-dimensional layered structure as a carrier and single-walled carbon nanotubes (SUVs) or sulfur-doped SUVs as a loading agent. The SUVs are mixed with the GeP nanosheets using a grinding process to initially modify the GeP nanosheets. Then, ultrasonication is used to further disperse the SUVs and GeP nanosheets evenly, allowing them to fill the interlayer spaces of the GeP nanosheets during subsequent drying. This prevents the aggregation of the GeP nanosheets. Simultaneously, the SUVs connect different GeP nanosheets, and the self-supporting effect of the SUVs constructs a three-dimensional conductive network structure, effectively improving the conductivity of the GeP-based electrode material. It also effectively accelerates the transport of sodium or lithium ions and electrons, overcoming the limitations of GeP-based electrode materials in Li... + Or Na + The volume expansion problem during the insertion and extraction process effectively improves the conductivity and resistance to volume expansion of GeP-based electrode materials, enabling them to be used as anode materials for lithium and sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930848A_ABST
    Figure CN122930848A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electrochemical energy storage, and discloses a germanium phosphide / carbon nanotube composite material, a preparation method and application thereof. The preparation method is as follows: single-walled carbon nanotubes or sulfur-doped single-walled carbon nanotubes are mixed with germanium phosphide nanosheets by grinding to obtain a precursor; the precursor is dispersed in ethanol by ultrasonic to obtain a suspension; the suspension is subjected to solid-liquid separation to obtain a precipitate, which is washed and dried to obtain the germanium phosphide / carbon nanotube composite material. The germanium phosphide / carbon nanotube composite material is obtained by combining germanium phosphide with single-walled carbon nanotubes, and the single-walled carbon nanotubes are self-supported to bond and embed the germanium phosphide together and form a three-dimensional conductive network, thereby improving the conductivity, overcoming the serious volume expansion of the germanium phosphide negative electrode material, and improving the conductivity and the anti-volume expansion capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage technology, and in particular to a germanium phosphide / carbon nanotube composite material, its preparation method, and its application. Background Technology

[0002] Energy storage devices are key to utilizing clean energy and reducing fossil fuel consumption. Among all rechargeable batteries, lithium-ion and sodium-ion batteries stand out for their high energy density and long cycle life, and have been widely used in portable electronic devices and electric vehicles.

[0003] Electrodes play a crucial role in the performance of lithium-ion batteries. In recent years, carbon-based materials have been the primary anode materials for lithium-ion and sodium-ion batteries. However, carbon-based materials have relatively low capacity, especially in terms of volumetric energy density.

[0004] To meet the high capacity requirements of lithium-ion and sodium-ion batteries, those skilled in the art have proposed that germanium has a high theoretical capacity, making germanium-based materials a promising alternative to the aforementioned carbon-based materials as anode materials for lithium-ion batteries. However, germanium-based materials experience severe volume expansion during charge-discharge cycles, leading to mechanical instability due to electrode pulverization and rapid capacity decay, thus limiting their application in lithium-ion and sodium-ion batteries.

[0005] Therefore, this invention proposes a germanium phosphide / carbon nanotube composite material, its preparation method, and its application. Summary of the Invention

[0006] To address the problem of severe volume expansion during charge-discharge cycling in existing germanium-based materials, leading to electrode pulverization, mechanical instability, and rapid capacity decay, this invention provides a germanium phosphide / carbon nanotube composite material, its preparation method, and its applications. For ease of description, germanium phosphide will be abbreviated as GeP in this invention. Furthermore, this invention proposes to improve the electrochemical performance of GeP-based electrodes by combining single-walled carbon nanotubes with GeP, or by combining sulfur-doped single-walled carbon nanotubes with GeP, thereby obtaining a more efficient and stable germanium phosphide / carbon nanotube composite material. This enables GeP-based electrodes to be used in lithium-ion and sodium-ion batteries.

[0007] The germanium phosphide / carbon nanotube composite material of the present invention, its preparation method and application are achieved through the following technical solutions:

[0008] The first objective of this invention is to provide a method for preparing germanium phosphide / carbon nanotube composite materials, comprising the following steps:

[0009] Step 1: Using GeP nanosheets with a two-dimensional layered structure as a carrier, and single-walled carbon nanotubes or sulfur-doped single-walled carbon nanotubes as a loading material, the loading material and GeP nanosheets are mixed by grinding. Through the grinding action, the loading material preliminarily modifies the GeP nanosheets to obtain a precursor.

[0010] It should be noted that this invention takes into account that GeP has a black phosphorus structure and a high concentration of 1914 mA·h·g. -1 Given its theoretical capacity, excellent conductivity, and high cycle reversibility, GeP is the preferred germanium-based material for preparing anode materials for lithium and sodium-ion batteries.

[0011] During the research process, this invention discovered that when GeP is directly used as the negative electrode material for lithium and sodium-ion batteries, the GeP electrode exhibits superior performance in Li... + Or Na + The insertion and extraction processes involve volume expansion, which affects the electrochemical performance of the battery. In other words, GeP-based electrode materials cannot be directly used as anode materials for lithium-ion and sodium-ion batteries. Therefore, in some preferred embodiments of this invention, single-walled carbon nanotubes are used as a support. The high flexibility and high conductivity of single-walled carbon nanotubes are used to modify GeP-based electrode materials, thereby improving the mechanical properties of the GeP electrode and ultimately enhancing its electrochemical performance.

[0012] During the research process, it was discovered that directly using the aforementioned loading material to modify bulk GeP structures is unsuccessful due to the difficulty in embedding and detaching ions and the limited number of reaction sites in bulk GeP, thus failing to achieve the intended effects of this invention. Therefore, in some preferred embodiments of this invention, two-dimensional layered GeP nanosheets are used as the carrier, and the two-dimensional layered GeP is smaller in size than bulk GeP, which is beneficial for subsequent composite with the loading material.

[0013] To ensure that the GeP nanosheets used in this invention have a two-dimensional layered structure, this invention attempts to use bulk GeP as a raw material, placing it in a solvent environment and exfoliating it using ultrasound, so as to obtain single-layer or few-layer bulk GeP under ultrasonic conditions. However, in actual operation, the inventors found that due to the strong van der Waals forces between the layers of bulk GeP, direct ultrasound exfoliation is difficult. Therefore, in some preferred embodiments of this invention, the GeP nanosheets are prepared through the following steps:

[0014] 1) After freezing the bulk GeP in liquid nitrogen, it is mixed with solvent to obtain a GeP mixture.

[0015] 2) The GeP mixture is subjected to ultrasonic treatment under ice-water bath conditions to exfoliate GeP, separate solid and liquid components, collect solid components, and obtain single-layer or few-layer GeP nanosheets, that is, to obtain GeP nanosheets with a two-dimensional layered structure.

[0016] It should be noted that in this invention, the bulk GeP is first frozen in liquid nitrogen, i.e., the bulk GeP is frozen with liquid nitrogen to increase its brittleness. Then, the brittle bulk GeP is mixed with a solvent. During the mixing process, small solvent molecules insert into the interlayer of the bulk GeP, which facilitates subsequent exfoliation. It is important to emphasize that during the freezing process in this invention, freeze-drying is performed for 5 minutes.

[0017] This invention does not limit the specific type of solvent, as long as the integrity of the GeP structure is maintained and no side reactions occur. For example, in some preferred embodiments of the invention, the solvent used can be selected from any one or more of N-methylpyrrolidone, ethanol and water.

[0018] To ensure that single-layer or few-layer two-dimensional layered GeP nanosheets can be obtained from bulk GeP through ultrasound, in some preferred embodiments of the present invention, the ultrasound power of the GeP mixture is 600W to 800W and the ultrasound time is 2h to 3h.

[0019] To ensure the modification of GeP nanosheets through the loading material, in some preferred embodiments of the present invention, it was discovered during the exploration process that when the amount of loading material is too small, it cannot effectively achieve composite with GeP nanosheets and cannot effectively prevent the self-aggregation of GeP nanosheets, thus failing to effectively improve the electrochemical performance of GeP-based electrode materials. Conversely, when the amount of loading material is too large, it causes the loading material to accumulate or agglomerate on the GeP nanosheets, thus failing to construct a three-dimensional conductive network structure and consequently failing to accelerate the transport of sodium or lithium ions and electrons. Therefore, based on this, the present invention preferably limits the mass ratio of the added loading material to the GeP nanosheets to 3-7:3-7, so that the loading material can fill the interlayer of the GeP nanosheets, thereby preventing the self-aggregation of GeP nanosheets. Simultaneously, the loading material connects different GeP nanosheets, and under the self-supporting effect of the loading material, a three-dimensional conductive network structure is constructed, thereby effectively improving the conductivity of the GeP-based electrode material and effectively accelerating the transport of sodium or lithium ions and electrons, overcoming the limitations of GeP-based electrode materials in Li... + Or Na +The volume expansion problem during the insertion and extraction process effectively improves the conductivity and resistance to volume expansion of GeP-based electrode materials, enabling them to be used as anode materials for lithium and sodium-ion batteries.

[0020] In some preferred embodiments of the present invention, the loading material and GeP nanosheets are mixed by grinding. This grinding process ensures uniform mixing of the loading material and GeP nanosheets, and further optimizes their sizes. This initial modification of the loading material and GeP nanosheets results in a better size match, facilitating more uniform dispersion and subsequent composite processing. Furthermore, in some preferred embodiments of the present invention, grinding is preferably used for mixing, and the grinding time is 20 to 40 minutes.

[0021] This invention does not limit the specific form of solid-liquid separation, as long as it can achieve the collection of solid components. In some feasible embodiments of this invention, solid-liquid separation is performed by centrifugation, with a centrifugation rate of 800 r / min to 1200 r / min and a centrifugation time of 10 min to 30 min.

[0022] To further improve the conductivity of single-walled carbon nanotubes and thus enhance the conductivity of the final composite material, sulfur-doped single-walled carbon nanotubes are used as the loading material in some preferred embodiments of the present invention. Furthermore, during the research process, it was found that when sulfur is directly doped into single-walled carbon nanotubes using vapor deposition, it is difficult to effectively achieve uniform sulfur doping. Therefore, in some preferred embodiments of the present invention, the sulfur-doped single-walled carbon nanotubes are obtained through the following steps:

[0023] 1) Using xenon difluoride as a modifier, xenon difluoride and single-walled carbon nanotubes were mixed at a mass ratio of 17–19:1 to obtain a mixture. Subsequently, the obtained mixture was annealed at 185–195°C for 20–30 hours under an argon atmosphere to introduce fluorine doping into the single-walled carbon nanotubes, replacing carbon atoms in the network and obtaining fluorine-doped single-walled carbon nanotubes. The fluorine-doped single-walled carbon nanotubes have more defects, which is beneficial for subsequent sulfur doping.

[0024] 2) Using vapor deposition, sulfur powder was placed in a quartz boat at the argon inlet of a tube furnace, and fluorine-doped single-walled carbon nanotubes were placed in another quartz boat at the argon outlet of the tube furnace. Before heating, the system was purged with argon at a rate of 80 sccm to 120 sccm for 20 to 40 minutes. Then, the argon was adjusted to provide a constant reaction atmosphere at a rate of 5 sccm to 15 sccm. The temperature was then raised to 380℃ to 410℃ and maintained at 380℃ to 410℃ for 8 to 12 minutes to release fluorine from the fluorine-doped single-walled carbon nanotubes, thereby creating vacancies on the surface of the single-walled carbon nanotubes. At the same time, sulfur vapor was generated during the heating process and purged to the fluorine-doped single-walled carbon nanotubes, reacting with the single-walled carbon nanotubes with vacancy defects on their surface and filling the vacancy defects, ultimately forming sulfur-doped single-walled carbon nanotubes.

[0025] This invention achieves in-situ doping of sulfur into single-walled carbon nanotubes (SHUs) without disrupting their inherent structure. By partially replacing carbon atoms in the network with sulfur, the conductivity of the SHUs is improved. This results in further enhanced conductivity of the composite material after subsequent compositing with GeP nanosheets, while also being more conducive to Li… + Or Na + The insertion and extraction of sodium or lithium ions further accelerates the transport of electrons, overcoming the limitations of GeP-based electrode materials in Li... + Or Na + The volume expansion problem during the insertion and extraction process effectively improves the conductivity and resistance to volume expansion of GeP-based electrode materials, enabling them to be used as anode materials for lithium and sodium-ion batteries.

[0026] Step 2: Disperse the precursor in ethanol using ultrasound to obtain a suspension.

[0027] It should be noted that, in some feasible embodiments of the present invention, the solvent used for ultrasonic dispersion can be any one of N-methylpyrrolidone, ethanol, and water. However, in order to facilitate subsequent separation of the solvent and the target analyte, and to avoid the possibility of the solvent damaging the GeP nanosheets during ultrasonication, it was found in actual exploration that when N-methylpyrrolidone is used as the solvent for ultrasonic dispersion, separation requires a high centrifugation speed and the separation effect is not good; when water is used as the solvent for ultrasonic dispersion, the water may cause changes in the structure of GeP under ultrasonic conditions. Therefore, in some preferred embodiments of the present invention, ethanol is used as the solvent so that the desired precipitate can be easily obtained by centrifugation while preserving the structure of the GeP nanosheets themselves.

[0028] As described above, the precursor obtained by this invention is a mixture of GeP nanosheets and single-walled carbon nanotubes, or a mixture of GeP nanosheets and sulfur-doped single-walled carbon nanotubes. To avoid self-agglomeration of GeP nanosheets and single-walled carbon nanotubes or sulfur-doped single-walled carbon nanotubes during the grinding process, which would prevent them from being fully mixed, this invention also employs ultrasonic dispersion of the precursor to ensure thorough and uniform mixing of the single-walled carbon nanotubes or sulfur-doped single-walled carbon nanotubes with GeP. This facilitates the formation of a germanium phosphide / carbon nanotube composite material with a uniformly distributed three-dimensional conductive network structure during subsequent processing. Furthermore, in some preferred embodiments of this invention, the ultrasonic power is 400–600 W to ensure appropriate power. And to further improve the dispersion effect, in some feasible embodiments of this invention, the ultrasonic duration is 1–2 hours.

[0029] To ensure that the amount of ethanol used is sufficient to uniformly disperse the precursor, in some feasible embodiments of the present invention, the ratio of ethanol to the precursor is 200 mL: 0.15 g to 0.25 g.

[0030] Step 3: Perform solid-liquid separation on the suspension to obtain a precipitate. Wash and dry the precipitate to obtain the germanium phosphide / carbon nanotube composite material.

[0031] It should be noted that, considering the ease of separation and operation, in some preferred embodiments of this invention, centrifugation is used for solid-liquid separation to obtain a precipitate. Furthermore, considering that the surface of the obtained precipitate may have residual impurities or solvents, it is also washed to remove interference from impurities. In some feasible embodiments of this invention, the centrifugation rate is 5000–8000 r / min, and the centrifugation time is 20–40 min.

[0032] This invention takes into account the influence of solvents on the lithium / sodium storage performance of GeP composite materials. In some feasible embodiments of this invention, the washed product is dried to remove residual washing liquid from the product surface, thereby obtaining a pure germanium phosphide / carbon nanotube composite material. To ensure that the above-mentioned effects can be achieved through drying, in some preferred embodiments of this invention, the drying temperature is 75℃~85℃, and the time is 20min~40min.

[0033] The second objective of this invention is to provide a germanium phosphide / carbon nanotube composite material prepared by the above-described preparation method.

[0034] The third objective of this invention is to provide an application of the above-mentioned germanium phosphide / carbon nanotube composite material in the preparation of lithium and sodium-ion battery anode materials.

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] This invention uses GeP nanosheets with a two-dimensional layered structure as a carrier and single-walled carbon nanotubes (SUVs) or sulfur-doped SUVs as a loading agent. The SUVs are mixed with the GeP nanosheets using a grinding process to initially modify the GeP nanosheets. Then, ultrasonication is used to further disperse the SUVs and GeP nanosheets evenly, allowing them to fill the interlayer spaces of the GeP nanosheets during subsequent drying. This prevents the aggregation of the GeP nanosheets. Simultaneously, the SUVs connect different GeP nanosheets, and the self-supporting effect of the SUVs constructs a three-dimensional conductive network structure, effectively improving the conductivity of the GeP-based electrode material. It also effectively accelerates the transport of sodium or lithium ions and electrons, overcoming the limitations of GeP-based electrode materials in Li... + Or Na + The volume expansion problem during the insertion and extraction process effectively improves the conductivity and resistance to volume expansion of GeP-based electrode materials, enabling them to be used as anode materials for lithium and sodium-ion batteries.

[0037] The preparation method of this invention is simple, easy to operate, safe, and controllable. The raw materials are inexpensive, and no binder is needed to achieve the composite of single-walled carbon nanotubes or sulfur-doped single-walled carbon nanotubes with GeP nanosheets, successfully constructing a germanium phosphide / carbon nanotube composite material with a three-dimensional conductive network structure. Furthermore, the prepared germanium phosphide / carbon nanotube composite material exhibits excellent electrochemical performance in lithium and sodium storage, possessing good specific capacity and cycle stability, and can be used as a negative electrode for lithium and sodium-ion batteries. Attached Figure Description

[0038] Figure 1 This is a scanning electron microscope image of the GeP nanosheets in Comparative Example 1.

[0039] Figure 2 The image shows an electron scanning microscope image of GeP / SWCNTs from Example 1.

[0040] Figure 3 The XRD pattern of GeP / SWCNTs in Example 1 is shown below. Figure 3 The illustrations in the text are Figure 3 A magnified view of the area within the dashed box.

[0041] Figure 4 The image shows the X-ray photoelectron spectrum of the S-SWCNTs prepared in Example 4.

[0042] Figure 5 The impedance test results are for GeP / SWCNTs of Example 1 and GeP nanosheets of Comparative Example 1.

[0043] Figure 6 The results are from the nanopressure constant test of GeP nanosheets in Comparative Example 1.

[0044] Figure 7 The results are from the nano-voltage constant test of the GeP / SWCNTs electrode in Example 1.

[0045] Figure 8 The charge-discharge curves are shown in the first two cycles when GeP / SWCNTs of Example 1 are used as the negative electrode of a lithium-ion battery.

[0046] Figure 9 The charge-discharge curves are shown in the first two cycles when GeP / SWCNTs from Example 1 are used as the negative electrode of a sodium-ion battery.

[0047] Figure 10 The results show the rate performance test results at different current densities when GeP / SWCNTs from Example 1 are used as the negative electrode of a lithium-ion battery.

[0048] Figure 11 The results show the rate performance test results at different current densities when GeP / SWCNTs from Example 1 are used as the negative electrode of a sodium-ion battery.

[0049] Figure 12 The results show the cycle stability test results when GeP / SWCNTs from Example 1 are used as the negative electrode of a lithium-ion battery.

[0050] Figure 13 The results show the cycle stability test results when GeP / SWCNTs from Example 1 are used as the negative electrode of a sodium-ion battery. Detailed Implementation

[0051] The technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be noted that the single-walled carbon nanotubes used in the following embodiments of the present invention were purchased from OCSiAl Company of Russia.

[0052] Example 1

[0053] This embodiment provides a germanium phosphide / carbon nanotube composite material, which is prepared by the following steps:

[0054] Step 1, Preparation of GeP nanosheets:

[0055] 1) After freezing the bulk GeP in liquid nitrogen, take 100 mg of the frozen bulk GeP and mix it with 100 mL of ethanol. Stir well to obtain a GeP mixture.

[0056] 2) Using a cell disruptor, the GeP mixture obtained above was ultrasonically treated for 3 hours under an ultrasonic power of 800W in an ice-water bath to exfoliate GeP through ultrasonic treatment. Subsequently, it was centrifuged at 1000r / min for 20 minutes, the precipitate was collected, and vacuum dried at 80℃ for 30 minutes to obtain GeP nanosheets.

[0057] Step 2, Preparation of precursors:

[0058] According to the mass ratio of GeP nanosheets to single-walled carbon nanotubes of 3:7, add the corresponding mass of single-walled carbon nanotubes to the GeP nanosheets obtained above, and grind them in a mortar for 20 minutes to make them fully mixed to obtain the precursor.

[0059] Step 3, Post-processing:

[0060] 1) Take 0.2g of the precursor obtained in step 2 above and disperse it in 200mL of ethanol to obtain a suspension.

[0061] 2) The suspension obtained above was centrifuged at a centrifugation rate of 6500 r / min for 30 min to obtain a precipitate. The precipitate was washed three times with deionized water and ethanol alternately, and then dried in a vacuum oven at 80℃ for 30 min to obtain germanium phosphide / carbon nanotube composite material, denoted as GeP / SWCNTs.

[0062] Example 2

[0063] This embodiment provides a germanium phosphide / carbon nanotube composite material, which is prepared by the following steps:

[0064] Step 1, Preparation of GeP nanosheets:

[0065] 1) After freezing the bulk GeP in liquid nitrogen, take 100 mg of the frozen bulk GeP and mix it with 100 mL of N-methylpyrrolidone, stir well, and obtain GeP mixture.

[0066] 2) Using a cell disruptor, the GeP mixture obtained above was ultrasonically treated for 2 hours under an ultrasonic power of 600W in an ice-water bath to exfoliate GeP through ultrasonic treatment. Subsequently, it was centrifuged at 800r / min for 30min, the precipitate was collected, and vacuum dried at 80℃ for 30min to obtain GeP nanosheets.

[0067] Step 2, Preparation of precursors:

[0068] According to the mass ratio of GeP nanosheets to single-walled carbon nanotubes of 5:5, add the corresponding mass of single-walled carbon nanotubes to the GeP nanosheets obtained above, and grind them in a mortar for 20 minutes to make them fully mixed to obtain the precursor.

[0069] Step 3, Post-processing:

[0070] 1) Take 0.15g of the precursor obtained in step 2 above and disperse it in 200mL of ethanol to obtain a suspension.

[0071] 2) Centrifuge the above-obtained suspension at a centrifugation rate of 5000 r / min for 30 min to obtain a precipitate. Wash the precipitate three times with deionized water and ethanol alternately, and then dry it in a vacuum oven at 80℃ for 30 min to obtain germanium phosphide / carbon nanotube composite material.

[0072] Example 3

[0073] This embodiment provides a germanium phosphide / carbon nanotube composite material, which is prepared by the following steps:

[0074] Step 1, Preparation of GeP nanosheets:

[0075] 1) After freezing the bulk GeP in liquid nitrogen, take 100 mg of the frozen bulk GeP and mix it with 100 mL of N-methylpyrrolidone, stir well, and obtain GeP mixture.

[0076] 2) Using a cell disruptor, the GeP mixture obtained above was ultrasonically treated for 3 hours under an ultrasonic power of 800W in an ice-water bath to exfoliate GeP through ultrasonic treatment. Subsequently, it was centrifuged at 1000r / min for 40min, the precipitate was collected, and vacuum dried at 80℃ for 30min to obtain GeP nanosheets.

[0077] Step 2, Preparation of precursors:

[0078] According to the mass ratio of GeP nanosheets to single-walled carbon nanotubes of 3:7, add the corresponding mass of single-walled carbon nanotubes to the GeP nanosheets obtained above, and grind them in a mortar for 40 minutes to make them fully mixed to obtain the precursor.

[0079] Step 3, Post-processing:

[0080] 1) Take 0.25g of the precursor obtained in step 2 above and disperse it in 200mL of ethanol to obtain a suspension.

[0081] 2) Centrifuge the above-obtained suspension at a centrifugation rate of 8000 r / min for 20 min to obtain a precipitate. Wash the precipitate three times with deionized water and ethanol alternately, and then dry it in a vacuum oven at 80℃ for 30 min to obtain germanium phosphide / carbon nanotube composite material.

[0082] Example 4

[0083] This embodiment provides a germanium phosphide / carbon nanotube composite material, which is prepared by the following steps:

[0084] Step 1, Preparation of GeP nanosheets:

[0085] 1) After freezing the bulk GeP in liquid nitrogen, take 100 mg of the frozen bulk GeP and mix it with 100 mL of ethanol. Stir well to obtain a GeP mixture.

[0086] 2) Using a cell disruptor, the GeP mixture obtained above was ultrasonically treated for 3 hours under an ultrasonic power of 800W in an ice-water bath to exfoliate GeP through ultrasonic treatment. Subsequently, it was centrifuged at 1000r / min for 20 minutes, the precipitate was collected, and vacuum dried at 80℃ for 30 minutes to obtain GeP nanosheets.

[0087] Step 2: Preparation of sulfur-doped single-walled carbon nanotubes:

[0088] 1) Single-walled carbon nanotubes and xenon difluoride were mixed at a mass ratio of 1:18, and then annealed at 190°C for 26 hours under an argon atmosphere to obtain fluorine-doped single-walled carbon nanotubes.

[0089] 2) Using vapor deposition, sulfur powder was placed in a quartz boat and positioned at the argon inlet of a tube furnace. Fluorine-doped single-walled carbon nanotubes were placed in another quartz boat and positioned at the argon outlet of the tube furnace. Before heating, the system was purged with argon at a rate of 100 sccm for 30 min. Then, the argon was adjusted to provide a constant reaction atmosphere at a rate of 10 sccm. The temperature was then raised to 400 °C and held at 400 °C for 10 min to obtain sulfur-doped single-walled carbon nanotubes, denoted as S-SWCNTs.

[0090] Step 3, Preparation of precursors:

[0091] According to the mass ratio of GeP nanosheets to sulfur-doped single-walled carbon nanotubes of 3:7, the corresponding mass of sulfur-doped single-walled carbon nanotubes was added to the GeP nanosheets obtained above, and the mixture was ground in a mortar for 20 minutes to ensure thorough mixing and obtain the precursor.

[0092] Step 4, Post-processing:

[0093] 1) Take 0.2g of the precursor obtained in step 2 above and disperse it in 200mL of ethanol to obtain a suspension.

[0094] 2) The suspension obtained above was centrifuged at a centrifugation rate of 6500 r / min for 30 min to obtain a precipitate. The precipitate was washed three times with deionized water and ethanol alternately, and then dried in a vacuum oven at 80℃ for 30 min to obtain germanium phosphide / carbon nanotube composite material, denoted as GeP / S-SWCNTs.

[0095] Comparative Example 1

[0096] This comparative example provides a germanium phosphide material, which is prepared by the following steps:

[0097] 1) After freezing the bulk GeP in liquid nitrogen, take 100 mg of the frozen bulk GeP and mix it with 100 mL of N-methylpyrrolidone, stir well, and obtain GeP mixture.

[0098] 2) Using a cell disruptor, the GeP mixture obtained above was ultrasonically treated for 3 hours under an ultrasonic power of 800W in an ice-water bath to exfoliate GeP through ultrasonic treatment. Subsequently, it was centrifuged at 1000r / min for 20 minutes, the precipitate was collected, and the GeP nanosheets were obtained by vacuum drying.

[0099] The only difference between this comparative example and Example 1 is that:

[0100] This comparative example does not contain composite single-walled carbon nanotubes.

[0101] Experimental Section

[0102] (I) Morphological Test

[0103] This invention uses GeP nanosheets obtained in Comparative Example 1 and GeP / SWCNTs from Example 1 as examples, and performs electron scanning microscopy tests on them. The test results are as follows: Figure 1 and Figure 2 As shown.

[0104] in, Figure 1 Here are scanning electron microscope images of GeP nanosheets obtained in Comparative Example 1. Figure 2 The image shows an electron scanning microscope image of GeP / SWCNTs from Example 1.

[0105] Depend on Figure 1 It can be seen that the GeP nanosheets obtained by the method of this invention are single-layer or few-layer nanosheet structures. And from... Figure 2 It can be seen that, relative to Figure 1In the GeP / SWCNTs prepared in Example 1 of this invention, GeP nanosheets are uniformly wrapped by single-walled carbon nanotubes, forming a three-dimensional conductive network structure.

[0106] (II) XRD Testing

[0107] This invention takes GeP / SWCNTs from Example 1 as an example and performs XRD tests on them, and the test results are as follows: Figure 3 As shown. Figure 3 The XRD pattern of GeP / SWCNTs in Example 1 is shown below. Figure 3 The illustrations in the text are Figure 3 A magnified view of the area within the dashed box.

[0108] Depend on Figure 3 and Figure 3 As shown in the illustrations, the GeP / SWCNTs prepared in Example 1 of this invention exhibit diffraction peaks at 13.9°, 21.1°, and 26.8°, corresponding to the (20-1), (20-2), and (111) crystal planes of GeP. The GeP in the GeP / SWCNTs retains its original structure, without forming a new phase. This indicates that the GeP / SWCNTs prepared in this invention possess excellent structural stability.

[0109] (III) X-ray photoelectron spectroscopy

[0110] This invention takes the sulfur-doped single-walled carbon nanotubes prepared in Example 4 as an example, and performs X-ray photoelectron spectroscopy (XPS) on them. The test results are as follows: Figure 4 As shown.

[0111] Depend on Figure 4 As can be seen, the X-ray photoelectron spectrum of the sulfur-doped single-walled carbon nanotubes prepared in Example 4 shows the presence of peaks corresponding to S2p and S1s. This indicates that the preparation method of the present invention can indeed achieve sulfur doping in single-walled carbon nanotubes to obtain sulfur-doped single-walled carbon nanotubes.

[0112] (III) Impedance Testing

[0113] This invention uses GeP / SWCNTs from Example 1 and GeP nanosheets from Comparative Example 1 as examples, and performs impedance tests on them respectively. The test results are as follows: Figure 5 As shown.

[0114] The testing method was as follows: 2032 coin cells were assembled, and electrochemical impedance spectroscopy was performed using a Shanghai Chenhua electrochemical workstation (CHI760) with a frequency range of 10 Hz. -2 Hz~10 5 Hz.

[0115] And by Figure 5The test results show that the impedance of the GeP / SWCNTs electrode is lower than that of the GeP electrode, indicating that the CNTs conductive network helps to improve the conductivity of GeP.

[0116] The present invention also conducted impedance tests on the GeP / S-SWCNTs obtained in Example 4 according to the above test method, and the test results showed that the impedance of GeP / S-SWCNTs was 81% to 83% of that of the GeP / SWCNTs electrode. This indicates that sulfur doping can further reduce the impedance of the electrode material and further improve the conductivity of GeP.

[0117] (iv) Nanoparticle pressure constant experiment

[0118] This invention uses GeP / SWCNTs from Example 1 and GeP nanosheets from Comparative Example 1 as examples, and conducts nanoscale pressure constant experiments on them respectively. The test results are as follows: Figure 6 and Figure 7 As shown.

[0119] The testing method was as follows: Nanomechanics was studied using the NanoTestVantage system. A triangular wedge indenter with a passivation radius of 100 nm was used. Three test points were selected for each sample, labeled as point1, point2, and point3, with loading, holding, and unloading times of 25 s, 5 s, and 10 s, respectively.

[0120] in, Figure 6 The results of the nano-pressure constant test of GeP nanosheets in Comparative Example 1 are shown. Figure 7 The results are from the nano-voltage constant test of the GeP / SWCNTs electrode in Example 1.

[0121] And through comparison Figure 6 and Figure 7 It can be seen that GeP / SWCNTs have a larger Young's modulus and stronger resistance to deformation. This indicates that GeP / SWCNTs, due to their three-dimensional network structure, have better resistance to volume expansion.

[0122] (V) Electrochemical Performance Testing

[0123] 1) Charge and discharge performance test

[0124] In this invention, GeP / SWCNTs from Example 1 were used as the negative electrodes for both lithium-ion and sodium-ion batteries, and cycle tests were performed on them. The first two cycles were designated as 1st and 2nd, respectively. The charge-discharge curves of GeP / SWCNTs from Example 1 in the first two cycles are shown below. Figure 8 and Figure 9 As shown.

[0125] Test method: Assemble a 2032 coin cell battery, using GeP / SWCNTs as the negative electrode and lithium or sodium foil as the counter electrode. Perform charging tests using the Xinwei Battery Test System, with a voltage range of 0.005–3V.

[0126] Figure 8 When GeP / SWCNTs from Example 1 are used as the negative electrode of a lithium-ion battery, the charge-discharge curves in the first two cycles show obvious plateaus in the ranges of 0.61–0.74V, 0.43–0.6V, and 0.1–0.3V. The plateaus in the first two cycles are similar, indicating that the lithium storage process is reversible.

[0127] Figure 9 The charge-discharge curves of the first two cycles when GeP / SWCNTs of Example 1 were used as the negative electrode of a sodium-ion battery show that there are obvious plateaus in the ranges of 0.79–0.45V and 0.3–0.01V, and the plateaus in the first two cycles are similar, indicating that the sodium storage process is reversible.

[0128] 2) Ratio Performance Test

[0129] This invention uses GeP / SWCNTs from Example 1 as the negative electrode for lithium-ion batteries and sodium-ion batteries, respectively, and studies their performance at 0.2 A·g. -1 1A·g -1 2A·g -1 and 4A·g -1 The rate performance at different current densities was tested, and the test results are as follows: Figure 10 and Figure 11 As shown.

[0130] Test method: A 2032 coin cell was assembled, using GeP / SWCNTs as the negative electrode and lithium or sodium foil as the counter electrode. Charging tests were conducted using the Xinwei Battery Test System at 0.2 A·g. -1 1A·g -1 2A·g -1 and 4A·g -1 They were charged and discharged at different current densities, with a voltage range of 0.005 to 3V.

[0131] Figure 10 The results show the rate performance test results of using GeP / SWCNTs from Example 1 as the negative electrode of a lithium-ion battery at different current densities. It can be seen that in lithium-ion batteries, when the current density is 0.2 A·g... -1 1A·g -1 2A·g -1 and 4A·g -1 At that time, they can maintain 633 mA·h·g respectively-1 429mA·h·g -1 307mA·h·g -1 348mA·h·g -1 and 198mA·h·g -1 The reversible capacity. When the current density returns to 0.2 A·g -1 At that time, the capacity also returned to 520 mA·h·g -1 GeP / SWCNTs electrodes still maintain good rate performance in lithium-ion batteries.

[0132] Figure 11 The results show the rate performance of the GeP / SWCNTs electrode in Example 1 as the negative electrode of a sodium-ion battery at different current densities. It can be seen that in sodium-ion batteries, the GeP / SWCNTs electrode exhibits good rate performance at high current densities (4 A·g⁻¹). -1 At that time, it can still maintain 80 mA·h·g -1 The specific capacity. When the current density drops to 0.2 A·g -1 At that time, the specific capacity returned to 354 mA·h·g -1 These results indicate that GeP / SWCNTs exhibit good rate performance as a negative electrode in sodium-ion batteries.

[0133] The present invention also tested the rate performance of GeP / S-SWCNTs obtained in Example 4 as lithium-ion battery anodes and sodium-ion battery anodes at different current densities according to the above-described test method. The test results showed that when GeP / S-SWCNTs were used as lithium-ion battery anodes, the rate performance at high current densities of 4 A·g⁻¹ was achieved. -1 At that time, its specific capacity was increased by 11% compared to GeP / SWCNTs in Example 1. When GeP / S-SWCNTs were used as the anode of a sodium-ion battery, at a high current density of 4 A·g -1 At that time, its specific capacity was increased by 18% compared to GeP / SWCNTs in Example 1. This indicates that sulfur doping can further improve the rate performance of the electrode material.

[0134] 3) Cyclic stability test

[0135] In this invention, GeP / SWCNTs from Example 1 were used as the negative electrode for both lithium-ion and sodium-ion batteries, and their cycle stability was tested. The test results are as follows: Figure 12 and Figure 13 As shown.

[0136] Test method: Assemble a 2032 coin cell battery, using GeP / SWCNTs as the negative electrode and lithium or sodium foil as the counter electrode. Conduct charging tests using Xinwei Battery Testing, with a voltage range of 0.005-3V, for 200 cycles.

[0137] Figure 12 The results of the cycle stability test using GeP / SWCNTs from Example 1 as the negative electrode of a lithium-ion battery show that GeP / SWCNTs exhibits a high first-cycle coulombic efficiency of approximately 85% and a performance of 778 / 911 mA·h·g as the negative electrode of a lithium-ion battery. -1 The specific capacity was [value missing]. After 10 cycles, the GeP / SWCNTs electrode tended to stabilize, and after 200 cycles, the specific capacity remained at 456 mA·h·g. -1 GeP / SWCNTs exhibit better coulombic efficiency and cycle stability than pure GeP electrodes.

[0138] Figure 13 The results of the cycle stability test using GeP / SWCNTs from Example 1 as the negative electrode of a sodium-ion battery show that GeP / SWCNTs achieves a high stability of 719 / 793 mA·h·g in sodium-ion batteries. -1 It exhibits high initial specific capacity and approximately 90% coulombic efficiency. After 200 cycles, it still maintains 397 mA·h·g. -1 Specific capacity. GeP / SWCNTs exhibited superior electrochemical performance.

[0139] Obviously, the above embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A method for preparing a germanium phosphide / carbon nanotube composite material, characterized in that, Includes the following steps: Using germanium phosphide nanosheets with a two-dimensional layered structure as a carrier, and single-walled carbon nanotubes or sulfur-doped single-walled carbon nanotubes as a loading material, the loading material and germanium phosphide nanosheets are mixed by grinding. Through the grinding action, the loading material preliminarily modifies the germanium phosphide nanosheets to obtain a precursor. The precursor was dispersed in ethanol by ultrasound to obtain a suspension; Then, the suspension is subjected to solid-liquid separation to obtain a precipitate. The precipitate is washed and dried to obtain the germanium phosphide / carbon nanotube composite material.

2. The preparation method according to claim 1, characterized in that, The germanium phosphide nanosheets are obtained through the following steps: Bulk germanium phosphide is frozen in liquid nitrogen to increase its brittleness, thus obtaining frozen bulk germanium phosphide. The frozen germanium phosphide bulk was mixed with a solvent to obtain a germanium phosphide mixture. Subsequently, the germanium phosphide mixture was subjected to ultrasonic treatment under ice-water bath conditions to exfoliate the germanium phosphide, separate the solid and liquid components, collect the solid components, and obtain the germanium phosphide nanosheets.

3. The preparation method according to claim 2, characterized in that, The solvent is any one or more of N-methylpyrrolidone, ethanol, and water.

4. The preparation method according to claim 2, characterized in that, When the germanium phosphide mixture is subjected to ultrasonic treatment, the ultrasonic power is 600W to 800W. The freezing time is 3 to 7 minutes.

5. The preparation method according to claim 1, characterized in that, The mass ratio of the loading material to the germanium phosphide nanosheets is 3-7:3-7.

6. The preparation method according to claim 1, characterized in that, The ratio of ethanol to the precursor is 200 mL: 0.15 g to 0.25 g.

7. The preparation method according to claim 1, characterized in that, The power of the ultrasound is 400W to 600W.

8. The preparation method according to claim 1, characterized in that, The sulfur-doped single-walled carbon nanotubes are prepared by the following steps: 1) Using xenon difluoride as a modifier, xenon difluoride is mixed with single-walled carbon nanotubes to obtain a mixture; the mixture is annealed at 185℃~195℃ under an argon atmosphere to introduce fluorine into the single-walled carbon nanotubes to obtain fluorine-doped single-walled carbon nanotubes. The mass ratio of xenon difluoride to single-walled carbon nanotubes is 17–19:

1. 2) Using vapor deposition, sulfur powder was placed in a quartz boat and placed at the argon inlet of a tube furnace. Fluorine-doped single-walled carbon nanotubes were placed in another quartz boat and placed at the argon outlet of the tube furnace. The argon purging rate was set to 5 sccm to 15 sccm. The temperature was raised to 380℃ to 410℃ and held for 8 min to 12 min to obtain sulfur-doped single-walled carbon nanotubes.

9. A germanium phosphide / carbon nanotube composite material prepared by the preparation method according to any one of claims 1-8.

10. The application of the germanium phosphide / carbon nanotube composite material of claim 9 in the preparation of anode materials for lithium and sodium-ion batteries.